Actual Modern Problems of Picture Coding (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides detailed information on the latest digital image encoding problems and their solutions. The software and hardware requirements for optimizing the size and quality of digital images are reviewed, as well as the role of artificial intelligence and machine learning technologies in the field. The article also discusses the future directions of digital image coding, including the need to develop new algorithms and coding standards for ultra-high resolution images. The problems of applying new technologies, which are important in improving the efficiency of coding, are also considered.